Correlation of Competency, Remuneration, Country Location and the Interest of Indonesian Nurses to Work Abroad - Sukartana, Sukartana; Indasah, Indasah (YCMM, 2024)
The nursing professional employment crisis in developed countries impacts the increasing demand for nurses in the largest nurse-producing countries. This study explores whether there is a correlation between competency, remuneration, and location on nurses' interest in working abroad. This research used quantitative methods with a correlational design. The population is 132 nurses and nursing students. The instrument used was a questionnaire prepared with a Likert Scale. Cronbach alpha was used to measure its validity. The dependent variables in this research were competence, remuneration, and location, while the independent variables were nurses' interests. The data processing used SPSS version 25 and was analyzed using Pearson's Correlation. The study shows The correlation coefficient values are 0.799; 0.850; and 0.863, which means the correlation between nurses' competencies, remuneration, and country location with the nurses' interest in working abroad is in the